2017
DOI: 10.1177/2396987317698328
|View full text |Cite
|
Sign up to set email alerts
|

Patients with acute stroke are less likely to be admitted directly to a stroke unit when hospital beds are scarce: A Swedish multicenter register study

Abstract: Introduction: It is well established that managing patients with acute stroke in dedicated stroke units is associated with improved functioning and survival. The objectives of this study are to investigate whether patients with acute stroke are less likely to be directly admitted to a stroke unit from the Emergency Department when hospital beds are scarce and to measure variation across hospitals in terms of this outcome. Patients and methods: This register study comprised data on patients with acute stroke ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Similar to DTN time, admission directly to a SU from the ED is expected to be predominantly related to organizational factors (such as hospital bed availability and regional guidelines) and therefore accessible to interventions . We found that direct SU admission showed a pronounced sequential pattern across both days of the week and time of day, where we especially want to emphasize that admission rates drop during nighttime.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Similar to DTN time, admission directly to a SU from the ED is expected to be predominantly related to organizational factors (such as hospital bed availability and regional guidelines) and therefore accessible to interventions . We found that direct SU admission showed a pronounced sequential pattern across both days of the week and time of day, where we especially want to emphasize that admission rates drop during nighttime.…”
Section: Discussionmentioning
confidence: 80%
“…Community hospitals showed the best absolute rates of direct SU admission, which probably can be attributed to organizational factors since Swedish community hospitals in general have more SU beds per capita than more specialized hospitals . We hypothesize that keeping more staff on duty during weekends (to improve discharge capabilities), increasing overall bed capacity, and implementing guidelines that prioritize stroke patients for admission to a stroke unit all could increase SU admission rates . Comparing temporal resiliency, university hospitals were significantly more resilient to variation for evening admissions compared to specialized non‐university hospitals.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Unfortunately, our study shows a decreased rate of stroke unit admissions over time, where university hospitals alone accounted for this decrease. We believe the reason for this is a shortage of hospital beds, as shown in our previous work (23), since university hospitals have fewer stroke unit beds per capita than specialized non-university hospitals and community hospitals (24). The solution to this problem is likely multifactorial.…”
Section: Discussionmentioning
confidence: 74%
“…As transfers to stroke centers continue to increase, there is a greater potential for hospital crowding, which has been shown to delay stroke unit admission. 28 Moreover, Rincon et al found that delayed admission to the neuro-ICU for critically ill stroke patients was associated with poor outcomes at discharge. 29 Our findings suggest the need for hospitals, critical care transport services, and other healthcare providers to consider both place and time when planning and coordinating acute stroke triage.…”
Section: Discussionmentioning
confidence: 99%